What is wrong with workism? - HAMMERTON, Matthew (Institutional Knowledge at Singapore Management University, 2025)
Workism is the phenomenon of people making their work the primary source of meaning and identity in their life. Recent critics of workism have argued that there is a growing trend towards it in many societies and that this is a bad thing. This article brings a philosophical perspective to the debate on workism. It develops a precise account of what workism is and evaluates the main objections raised against it by examining their underlying philosophical assumptions. Ultimately, it is argued that workism, as a way of life, is not as objectionable as its critics suggest.